2022
DOI: 10.3390/buildings12050575
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Mechanism of Fire Spread between Full-Scale Wooden Houses from Internal Fires

Abstract: In ancient villages, the spread of uninterrupted fires caused great damage to clustered wooden houses. Thus, the spread of fire among wooden houses should be systematically studied to explore its characteristics. Statistical analysis is a feasible way to study the characteristics and underlying mechanisms of fire in full-scale wooden houses. In this study, 4 full-scale wooden buildings were built in an ethnic village in Guizhou Province, and the fire spread test was conducted by igniting a 0.63-MW power wood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Scholars have also researched the spread of fires in ancient timber structure complexes. In ancient villages, the spread of uninterrupted fires caused significant damage to timber structure complexes [107]. Yuan et al [107] studied the characteristics and underlying mechanisms of fire in full-scale timber houses.…”
Section: Flame Characteristics In Timber Structurementioning
confidence: 99%
See 3 more Smart Citations
“…Scholars have also researched the spread of fires in ancient timber structure complexes. In ancient villages, the spread of uninterrupted fires caused significant damage to timber structure complexes [107]. Yuan et al [107] studied the characteristics and underlying mechanisms of fire in full-scale timber houses.…”
Section: Flame Characteristics In Timber Structurementioning
confidence: 99%
“…In ancient villages, the spread of uninterrupted fires caused significant damage to timber structure complexes [107]. Yuan et al [107] studied the characteristics and underlying mechanisms of fire in full-scale timber houses. The results showed that, in timber houses, fire spread was mainly influenced by the slope, the distance between places, and wind direction [107].…”
Section: Flame Characteristics In Timber Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Densified wood has excellent mechanical performance, higher than many traditional construction materials, presenting promising potential in applications in medium-and high-rise timber buildings [6,7]. Nevertheless, the fire safety of densified wood is hardly known, and due to the flammable nature of wood [8,9], it deserves to be investigated to improve its application. The results would be significant for evaluating the fire behavior of wooden structures constructed with dense wood.…”
Section: Introductionmentioning
confidence: 99%